Silicon Improves Heat and Drought Stress Tolerance Associated with Antioxidant Enzyme Activity and Root Viability in Creeping Bentgrass (Agrostis stolonifera L.) - Xunzhong Zhang; Mike Goatley; Kehua Wang; Ben Goddard; Rose Harvey; Isabel Brown; Kelly Kosiarski (Agronomy, 2024)
Creeping bentgrass (Agrostis stolonifera L.) is an important cool-season turfgrass species widely used for golf course putting greens; however, it experiences summer stress and quality decline in the U.S. transition zone and other regions with similar climates. Silicon (Si) may improve the abiotic stress of creeping bentgrass, but the mechanism of its impact on plant drought and heat tolerance is not well understood, and a few studies have reported on the effects of Si on creeping bentgrass drought and heat tolerance. The objectives of this study were to determine the effects of Ortho-silicic acid (Ortho-Si) on antioxidant metabolism and root growth characteristics and viability in creeping bentgrass under drought and heat-stress conditions. The three treatments, including control, Ortho-Si at 0.16 mL m−2 and 0.32 mL m−2, were applied biweekly to creeping bentgrass. Foliar application of the Ortho-Si exhibited beneficial effects on turf quality, physiological fitness, and root growth in creeping bentgrass. The Ortho-Si application at 0.16 mL m−2 and 0.32 mL m−2 improved turf quality ratings by 9.5% and 11.1%, respectively, photochemical efficiency (PE) by 6.9% and 8.5%, respectively, chlorophyll content by 27.1% and 29.9%, and carotenoids content by 25.5% and 27.2%, respectively, when compared to the control at the end of the trial. The Ortho-Si treatments enhanced antioxidant enzyme activity; the highest amount, in particular, increased superoxide dismutase (SOD) activity by 32.8%, catalase (CAT) by 12.8%, and ascorbate peroxidase (APX) activity by 37.4%, as compared to the control. The Ortho-Si application reduced leaf hydrogen peroxide (H2O2) concentration relative to the control. In addition, exogenous Ortho-Si improved leaf Si concentration. The Ortho-Si application at 0.32 mL m−2 increased root biomass by 52.7% and viability by 89.3% relative to the control. Overall, Ortho-Si at 0.32 mL m−2 had greater beneficial effects than the low rate (0.16 mL m−2). Exogenous Si may improve drought and heat tolerance by protecting photosynthetic function, enhancing the activities of leaf antioxidant enzymes, and stimulating root growth, viability, and Si uptake. The results of this study suggest that foliar application of Ortho-Si at 0.32 mL m−2 may be considered to be an effective approach to improve turf quality and physiological fitness of creeping bentgrass during the summer months in the U.S. transition zone and other regions with similar climates.